Telecommunications Reform : How to Succeed - Wellenius, Björn (World Bank, Washington, DC, 2012)
Telecommunications Reform -privatization and opening markets to competition- can be a positive-sum game in which all stakeholders gain: customers, existing and new operators, employees, domestic and foreign investors, and government. But the extent and timing of benefits vary from one case to another. The author sets out some rules for reform that will enhance those benefits: Get support at the highest level of political authority. Sort out conflicting objectives early especially the conflict between maximizing revenue and delivering more, better, and cheaper services. Use market mechanisms rather than individual negotiations to select the partners and determine the right sale price. Establish and follow clearly defined processes for sale and regulation that are open to participation and review by all interested parties. And respect and trust the general public and keep it informed. Although major transactions such as a privatization or the issuance of new licenses drive the reform agenda, change continues well beyond them. Following the rules and honoring commitments help consolidate an environment for sustainable development of telecommunications.